PERANCANGAN DAN PEMBUATAN E-COMMERCE SPARE PARTS MOTOR PADA UD. NEW 234 MOTOR - Aribawa, Made Rendy; Dewi, Lily Puspa; Gunawan, Ibnu (Jurnal Infra, 2013)
UD. New 234 motor is businesses engaged in the sale of spare parts and a variety of motorcycles in the village of Tinga - Tinga. Sales process still using manual system where the customer can only come directly to find out the latest stuff. In order to use the payment system still uses manual that customers make payments directly come to UD. New 234 Motor. With the e-commerce website is expected to provide a change of the system offline sales to online sales systems are computerized over issues such as the promotion of new goods and the payment process will be easier. Application of e-commerce is expected to make the sales process for the better and of course also expected to increase sales and provide many benefits for UD New 234 Motor.System designâs scheme use Data Flow Diagram and Entity Relationship Diagram. Database made by using PHPMyadmin. Program which has been made cover database master for members, books, book category, publisher, selling process transaction, and time-based report.Designing the system using the Data Flow Diagram and Entity Relationship Diagram. Database created using phpmyadmin. Program that includes creating a master database created for members, goods, sales, returns.From the test results, a program created to process sales data relating to the transaction at UD New 234 Motor.